Half-life : the divided life of Bruno Pontecorvo, physicist or spy - Close, F. E. (Basic Books, a member of the Perseus Books Group, 2015)
Bruno Pontecorvo dedicated his career to hunting for the Higgs boson of his day-- the neutrino, a nearly massless particle considered essential to the process of nuclear fission. His work on the Manhattan project under Enrico Fermi confirmed his reputation as a brilliant physicist and helped usher in the nuclear age. He should have won a Nobel Prize, but late in the summer of 1950 he vanished. At the height of the Cold War, Pontecorvo had disappeared behind the Iron Curtain. In Half-Life, physicist and historian Frank Close offers a heretofore untold history of Pontecorvo's life, based on unprecedented access to his friends, family, and colleagues. With all the elements of a Cold War thriller-- classified atomic research, an infamous double agent, a kidnapping by Soviet operatives-- Half-Life is a history of particle physics at perhaps its most powerful: when it created the bomb.